The Tension and Synergy of Ethical Sources in The Relations of Lecturers and Students in Indonesian Universities - Siti Syamsiyatun; Khanis Suvianita (Institut Agama Islam Negeri Madura, 2019)
Higher education is expected to be a place to nurture youth or young generation who is strong, devoted to God and able to work for humanity. However, this highly trusted institution still faces ambiguous ethical issues that are shown by the mental attitude and behaviour of lecturers and students, such as plagiarism, sexual harassment and other immoral acts. Various incidents of ethical violations can be found in private and public universities, which are affiliated with certain religions or not. This research investigates the source of ethical considerations which underlie the relationship between lecturers and students in realizing their spirit and dignity as academic community. This research was conducted in four cities, namely Yogyakarta, Jakarta, Surabaya and Ruteng, using a qualitative approach, with the interview method and FGD to gather information. The ethical framework theory of Ibn Miskawayh and Immanuel Kant is used to analyze the data found. The results showed a variety of ethical sources referred by lecturers and students in carrying out their participation in higher education; the most widely referred sources are informants from religion, culture and objective rationality. The data also shows the existence of this ethical reference contestation, for example in the case of violations of sexual ethics, the male and the lecturers are more advantageous than students and women because cultural ethics is more in favour of men. Although all universities studied have a professional code of ethics, the ethical integrity of individual lecturers and students is no less important to be strengthened.